ZYGOMYCOSIS WITH INVOLVEMENT OF THE LUNG IN CHILDREN - N. A. Il’ina; R. O. Terent’ev (Вестник рентгенологии и радиологии, 2017)
The paper describes a rare proven case of pulmonary zygomycosis as a complication of supersevere idiopathic acquired aplastic anemia in an 11-year-old child. The authors give the results, interpret computer tomography, radiographic, clinical, and laboratory data, and discuss the causes and clinical presentations of invasive zygomycosis and methods for its timely diagnosis. The case is of interest due to the atypical course and outcomes of the disease.